THE RELATIONSHIP BETWEEN THE INTENSITY OF ATTENDING GUIDANCE AND COUNSELING SERVICES AND STUDENTS' PERCEPTIONS OF GUIDANCE AND COUNSELING SERVICES - Betania Fitriani; Satrio Budi Wibowo; Tri Anjar (Counseling Milenial (CM), 2026)
Intensity is the seriousness or frequency with which students carry out activities to obtain maximum results from a guidance and counseling service activity. Meanwhile, perception is a response or assessment that varies from a stimulus object and produces a response so that there will be different responses or assessments from students towards guidance and counseling services. The aim of this research is to determine the relationship between the intensity of participating in guidance and counseling services and students' perceptions of guidance and counseling services. This type of research is quantitative correlational research. With a population of 212, the sample was taken using the stratified random sampling method. From this sampling method, there were a total sample of 47 students from classes X, XI and XII TJKT. The data obtained, namely the positive correlation between intensity and perception, was declared significant because the p-value was below 0.05, namely 0.013. Then the result of the product moment value of Pearson's r is 0.363. From these results, it can be concluded that there is a relationship between intensity and perception, but it is not close to a significance of 1%. So the relationship between intensity and perception will be closer and higher if the more often students participate in guidance and counseling service activities, the better the students' perception of guidance and counseling services.